2019
DOI: 10.1111/cas.14040
|View full text |Cite
|
Sign up to set email alerts
|

CADM1 associates with Hippo pathway core kinases; membranous co–expression of CADM1 and LATS2 in lung tumors predicts good prognosis

Abstract: Cell adhesion molecule‐1 (CADM1) is a member of the immunoglobulin superfamily that functions as a tumor suppressor of lung tumors. We herein demonstrated that CADM1 interacts with Hippo pathway core kinases and enhances the phosphorylation of YAP1, and also that the membranous co–expression of CADM1 and LATS2 predicts a favorable prognosis in lung adenocarcinoma. CADM1 significantly repressed the saturation density elevated by YAP1 overexpression in NIH3T3 cells. CADM1 significantly promoted YAP1 phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Moreover, RUXF and PGES2 are known to be involved in chemo-resistance in ovarian and colorectal cancer, respectively (18,19). On the other hand, CADM1 is shown to be a good prognostic marker in other cancers (20,21). Four proteins (i.e., TMED2, AGR2, JTB, and CADM1) among the over-expressed proteins in poor-responders ( Table 3) were predicted to be secreted extracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RUXF and PGES2 are known to be involved in chemo-resistance in ovarian and colorectal cancer, respectively (18,19). On the other hand, CADM1 is shown to be a good prognostic marker in other cancers (20,21). Four proteins (i.e., TMED2, AGR2, JTB, and CADM1) among the over-expressed proteins in poor-responders ( Table 3) were predicted to be secreted extracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that modest static pressure flattened epithelial cells and could inhibit their growth and slow the cell cycle through activation of YAP, a key transcriptional cofactor of the Hippo pathway [14]. In fact, CADM1 is shown to participate in the control of contact inhibition through the Hippo pathway in NIH3T3 fibroblastic cells and to form complexes with Hippo pathway core molecules LATS1, LATS2, MST1, and MST2 in HEK293 cells [30]. Clinically, co-expression of CADM1 and LATS2 on the cell membrane of cancer cells predicts good prognosis of lung adenocarcinoma [30].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CADM1 is shown to participate in the control of contact inhibition through the Hippo pathway in NIH3T3 fibroblastic cells and to form complexes with Hippo pathway core molecules LATS1, LATS2, MST1, and MST2 in HEK293 cells [30]. Clinically, co-expression of CADM1 and LATS2 on the cell membrane of cancer cells predicts good prognosis of lung adenocarcinoma [30]. Collectively, CADM1 downregulation may promote apoptosis through involving the Hippo pathway based on the molecular interactions immediately beneath the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…CADM1 (cell adhesion molecule‐1), also known as TSLC1, is expressed at the lateral membrane in normal epithelial cells 8,9 . CADM1 gene is a tumor suppressor and exerts a protect role in preventing malignant conversion and metastasis 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…CADM1 (cell adhesion molecule-1), also known as TSLC1, is expressed at the lateral membrane in normal epithelial cells. 8,9 CADM1 gene is a tumor suppressor and exerts a protect role in preventing malignant conversion and metastasis. 10,11 At present, more and more studies have demonstrated that CADM1 is related to cell proliferation, migration and invasion of various cancers, such as liver, 12 gastric 13 and breast cancers.…”
Section: Introductionmentioning
confidence: 99%